ESTUDO ETNOLINGUÍSTICO DAS PRÁTICAS SUPERSTICIOSAS REFERENTES À MULHER GRÁVIDA NA CULTURA POPULAR DO MARANHÃO | ETHNOLINGUISTIC STUDY OF SUPERSTECTIVE PRACTICES REGARDING PREGNANT WOMEN IN POPULAR CULTURE OF MARANHÃO - Matos, Heloísa Reis Curvelo (Estudos Linguísticos e Literários, 2019)
Resumo: Nossa visão de mundo diante da cultura do outro é avaliativa e carregada de criticidade. Por quê? A resposta ao questionamento buscamos na Etnolinguística, ramo da Linguística que estuda a relação entre língua, cultura e sociedade. Considerando o aporte teórico de Vasconcellos (1938), Vieira Filho (1953), Cosériu (1987) e Lima (1998), objetivamos investigar e analisar as práticas superstições referentes à mulher grávida na cultura popular do Maranhão, em municípios das Mesorregiões Norte e Leste, considerando tanto o conhecimento folclórico quanto o científico. Para tanto, fizemos pesquisa bibliográfica, entrevistas, a ficha do informante, o questionário; aplicação do questionário a 12 informantes perfiladas. Constatamos que há muitas práticas supersticiosas milenares e indiscutíveis. Abstract: Why is our world view in the face of the Other culture evaluative and charged with criticality? The answer to this question can be found in the Ethnolinguistic field which is a Linguistic branch that studies the relation between language, culture and society. Considering the theoretical contribution of Vasconcellos (1938), Vieira Filho (1953), Cosériu (1987) and Lima (1998), we aim to investigate and analyze superstitious practices regarding pregnant women in the popular culture of Maranhão in municipalities of North and East Mesoregions, considering both the folkloric and scientific knowledge. To this end, the study was based on bibliographic research and the data collected provided by the interviews of 12 profiled informants. As a result, we found that there are many superstitious practices that are millennial and indisputable Keywords: Ethnolinguistics; Maranhense popular culture; superstitious practices; pregnant woman.